An earthquake is a shaking of the surface of the earth : a novel - Moschovakis, Anna (Soft Skull, 2024)
"After a seismic event leaves the world shattered, an unnamed narrator at the end of a mediocre acting career struggles to regain the ability to walk on ground that is in constant motion. When her alluring younger housemate, Tala, disappears, what had begun as an obsession grows into an impulse to kill, forcing the narrator to confront the meaning of the ruptures that have suddenly upended her life. The drive to find and eliminate Tala becomes an existential pursuit, leading back in time and out into a desolate, dust-covered city, where the narrator is targeted by charismatic "healing" ideologues with uncertain motives. Torn between a gnawing desire to reckon with the forces that have made her and an immediate need to find the stability to survive, she is forced to question familiar figurations of light, shadow, authenticity, resistance, and the limits of personal transformation in an alienated, alienating world"--